Snapdragon - Leyh, Kat (First Second, 2020)
When Snap finds a litter of orphaned opossums, she brings them to Jacks, a strange woman who's rumored to be a witch. In return for taking care of the opossums, Snap agrees to help Jacks with her work. As Snap gets to know Jacks, she realizes that Jacks may in fact have actual magic, as well as an unlikely connection to Snap's own family.